1995
DOI: 10.1111/j.1442-9071.1995.tb00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute irreversible cataracts in diabetes mellitus

Abstract: Aim:To report an unusual cause of blindness in a patient newly diagnosed with insulin-dependent diabetes mellitis (IDDM). Method:A 19-year-old man presented with classical symptoms of hyperglycaemia. On presentation his visual acuity and ophthalmic examination were normal. He was prescribed twice-daily insulin therapy and six weeks later presented with visual loss. He had only light and dark perception and was noted to have bilateral, dense, mature cataracts.Outcome: Right cataract extraction and intraocular l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 6 publications
0
12
0
1
Order By: Relevance
“…Many studies, including case reports and population surveys, have also found associations between diabetes and all lens opacities 733 , very early or rapid-onset cortical opacities [747][748][749] , and cataract surgery [750][751][752] . Among 653 consecutive cataract surgical procedures in persons aged 60 years or older at Westmead Hospital in Sydney, 28% gave a diabetes history, a much higher proportion than seen for healthy patients at this age 753 .…”
Section: Cataract In Diabetesmentioning
confidence: 99%
“…Many studies, including case reports and population surveys, have also found associations between diabetes and all lens opacities 733 , very early or rapid-onset cortical opacities [747][748][749] , and cataract surgery [750][751][752] . Among 653 consecutive cataract surgical procedures in persons aged 60 years or older at Westmead Hospital in Sydney, 28% gave a diabetes history, a much higher proportion than seen for healthy patients at this age 753 .…”
Section: Cataract In Diabetesmentioning
confidence: 99%
“…In a Vietnamese long-term follow-up study, 50% of type 2 diabetics developed cataracts [8]. Mature dense cataracts are rare but, when they occur, do not appear to resolve with control of hyperglycemia [9]. Surgical removal is thus required.…”
Section: Diabetesmentioning
confidence: 99%
“…There are a small number of reports of bilateral cataracts developing soon after diagnosis of diabetes [2][3][4][5][6][7][8].…”
Section: Bilateral Early Cataracts Inmentioning
confidence: 99%
“…Cornwell et al [6] reported a case of 19 year old newly diagnosed patient of diabetes with normal ophthalmic examination at presentation, developing bilateral cataracts requiring surgery within six weeks. Seven of fourteen patients in the series of Wilson Jr et al [5] developed cataracts shortly after being diagnosed to have diabetes.…”
Section: Bilateral Early Cataracts Inmentioning
confidence: 99%